Risk Factors and Prognostic Value of Swirl Sign in Traumatic Acute Epidural Hematoma - Wang, Xuanzhi; Ge, Ruixiang; Yuan, Jinlong; Xu, Shanshui; Fang, Xinggen; Dai, Yi; Jiang, Xiaochun (Frontiers in Neurology, 2020)
Objective: Acute epidural hematoma (AEDH) is one of the most deadly lesions in patients after traumatic brain injury. AEDH with swirl sign progresses rapidly and requires timely surgical treatment. This study aims to investigate the risk factors for the occurrence of AEDH with swirl sign and its prognostic value. Methods: Retrospective analysis was performed on 131 AEDH patients, who were divided into swirl sign group and non-swirl sign group based on the brain computed tomographic (CT) scan. Patient information, including gender, age, hypertension, mechanism of injury, Glasgow Coma Scale (GCS) score on admission, time from injury to CT scan, pupillary light reactivity on admission, midline shift, location of hematoma, hematoma volume on admission, oral anticoagulation and Glasgow Outcome Scale (GOS) score at 3 months were collected. Univariate analysis was used to determine the risk factors for the occurrence of swirl sign. The factors with P value <0.05 were recruited into the multivariate logistic regression analysis and predictive receiver operating characteristic (ROC) curve model. Results: Univariate analysis demonstrated that the GCS score on admission(P=0.007), pupillary light reactivity (P=0.003), location of hematoma(P＜0.0001), and GOS score at 3 months(P=0.007) were risk factors for the occurrence of swirl sign. Multivariate logistic regression model revealed that the location of hematoma (OR=0.121; 95%CI: 0.019-0.786; P=0.027) was an independent risk factor for swirl sign, and the occurrence of swirl sign was a significant predictor of unfavorable neurological outcomes (OR=0.100; 95%CI: 0.016-0.630; P=0.014). ROC curves demonstrated that the GCS score on admission (AUC=0.655; 95%CI: 0.506-0.804), pupillary light reactivity(AUC=0.625; 95%CI: 0.474-0.777 ) and location of hematoma(AUC=0.788; 95%CI: 0.682-0.893 ) can predict the occurrence of swirl sign respectively. Remarkably, the combination of these three factors (AUC=0.829; 95% CI: 0.753-0.906 ) provided a greater power to predict the swirl sign. Conclusion: GCS score on admission, pupillary light reactivity, and location of hematoma are risk factors for the occurrence of swirl sign, respectively. The combination of these three factors might be used to predict whether there is swirl sign in AEDH after traumatic brain injury. Furthermore, swirl sign can be used as an effective predictor of poor prognosis in patients.